2015
DOI: 10.1007/s11250-015-0762-2
|View full text |Cite
|
Sign up to set email alerts
|

Study on evaluation of silage from pineapple (Ananas comosus) fruit residue as livestock feed

Abstract: Pineapple is a commercially important fruit crop grown in Asian and African countries. Pineapple fruit residue (PFR) accounts for more than 65% of the processed fruits, and its disposal is a major problem due to its high moisture and sugar content predisposing it to fungal growth and spoilage. Silage technique was adopted to address this problem, and the PFR silage was evaluated for its feeding value. It was observed that on 15th day, the pH of PFR silage was 4.2-4.3 and lactic acid content was 6-8% (DM basis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 8 publications
1
30
0
1
Order By: Relevance
“…In addition, the results of carcass weight confirmed the data published by Cutrim et al (2013) in which the final BW and daily weight gain were not affected by pineapple by-product silage feeding. Gowda et al (2015) also verified the same daily weight gain in lambs fed a pineapple by-product In regression equations "x" means "proportion of byproduct silage". silage diet, which, support desired growth rate and did not have any adverse effects on nutrient utilization and general health.…”
Section: Resultssupporting
confidence: 55%
“…In addition, the results of carcass weight confirmed the data published by Cutrim et al (2013) in which the final BW and daily weight gain were not affected by pineapple by-product silage feeding. Gowda et al (2015) also verified the same daily weight gain in lambs fed a pineapple by-product In regression equations "x" means "proportion of byproduct silage". silage diet, which, support desired growth rate and did not have any adverse effects on nutrient utilization and general health.…”
Section: Resultssupporting
confidence: 55%
“…Concerning the feed intake of cattle fed on PWS, Gowda et al [ 4 ] reported that replacement of PWS in Napier green fodder showed no significant effect on nutrient intakes of Holstein Friesian dairy cows. Moreover, Hattakum et al [ 5 ] also stated that the replacement of PWS in NGS decreased feed intake of Holstein steer.…”
Section: Resultsmentioning
confidence: 99%
“…As the preservation, ensiling has been considered for more extended storage of those materials. Ensiling of pineapple waste has benefits for improving the economics of feeding as well as overcoming the disposal problem [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste trabalho não foram verificadas alterações nos padrões de atividades destas enzimas demonstrando assim que a dieta exclusiva de melão provavelmente não provocou danos significativos ao fígado que comprometesse a função desse órgão na manutenção metabólica dos animais deste experimento. Gowda et al (2015), ao examinarem a possibilidade de usar o resíduo fermentado de abacaxi na alimentação de animais como um novo recurso alimentar verificaram que os parâmetros bioquímicos do sangue AST e ALT (139 e 19.5 UI/L, respectivamente) não diferiram significativamente entre os grupos de borregos alimentados com milho ou silagem de abacaxi e os valores estavam dentro da faixa fisiológica, sugerindo que a alimentação com a silagem não teve nenhum efeito adverso na saúde geral dos cordeiros. Rizzo et al (2015), ao relatarem um caso de indigestão causado pela ingestão de manga (Mangifera indica) por uma vaca leiteira (¾ holandês x ¼ Gir), observaram que o consumo excessivo e não adaptado da fruta, sendo retirados 174 caroços do rúmen do animal, apresentou, através do exame bioquímico, resultado que denota o comprometimento hepático (ALT: 26 UI/L e AST 460 UI/L).…”
Section: Resultsunclassified